SITE-DIRECTED MUTAGENESIS OF THE BACTERIAL PHYTASE GENE COMPATIBLE FOR CHICKEN CODON PREFERENCES - F. Rashidi Khorasgani; S. Eghbalsaied (Journal of Animal and Plant Sciences, 2015)
Phytases are among a special group of phosphatase enzymes that catalyze the stepwise hydrolysis of phytic acid and release a usable form of inorganic phosphorus. Currently, in order to increase the absorption of dietary phosphorus and decreasing the phosphorus pollution in the environment, phytase could be supplemented to the diet of monogastric animals including pig, poultry and fish. Commercially available exogenous phytases are commonly derived from either fungi, yeasts or bacteria, Nevertheless, E. coli bacteria is one of the main sources of phytase expression, that produces a type of phytase which is  resistant to pepsin hydrolysis in the stomach of most animals, and also has a high specific activity for hydrolzying phytic acid. The aim of this study was the isolation of the bacterial phytase gene and optimizing its encoding sequences for efficient expression in chicken. At the first step, through specific primers, cloning of this gene was achieved by insertion of the DNA fragment encompassing bacterial phytase gene to pTG19 vector. This fragment was then inserted into the pIRES-hrGFP-vector.  This recombinant vector is suitable for further analyses to investigate the expression of the phytase gene along with the EGFP transgene.
Keywords: Phytase; E. coli; codon bias; IRES vector; chicken